Modified efficiency-based Bee Algorithm - Houssein, Firas Aimanovich; Kostyukov, Vladimir Alexandrovich (International Conference on Control, Decision and Information Technologies (Online), 2022)
A modification on the search strategy of the bee algorithm that improves its overall performance is presented in this work. We propose efficiency-based recruitment process of the bees that perform the local search. Both the original and the modified algorithms were tested on a benchmark optimization problems and an additional statistical analysis was performed. Although the advantage varies between different comparison modules, the modified algorithm always provides an advantage in terms of the calculation time. Further, both the original and the modified algorithms were implemented to solve the problem of optimal control of an unmanned aerial vehicle; the algorithms were used for synthesizing a linear-quadratic regulator LQR. The obtained simulation results showed that the proposed modification improved the overall performance of the bee algorithm and made it more time-efficient.